Mathematical, theoretical and phenomenological challenges beyond the standard model : (World Scientific, 2005)
This book contains invited lectures and shorter contributions to the workshop ‘Mathematical, Theoretical and Phenomenological Challenges Beyond the Standard Model: Perspectives of the Balkan Collaborations’ (BW2003), which was held in Vrnjačka Banja, Serbia, 29 August – 3 September. It was one of the first high-level HEP workshops in the South-East European region after many years, and the papers give a clear perspective on the scientific potential of this area. The contributions cover topics and problems under research in high-energy particle physics and quantum field theory, in particular: string theory and M-theory; grand unification; quantum gravity and cosmology; standard and noncommutative quantum field theory.